Aluminum stress inhibits accumulation of phosphorus in root apices of aluminum-sensitive but not aluminum-resistant brachiaria cultivar - Wenzl, Peter; Mayer, Jorge Edgard; Rao, Idupulapati M. (Informa UK Limited, 2002)
The phosphorus (P) content of whole roots and root apices has been reported to increase under aluminum (Al) stress, particularly in Al-sensitive plant varieties. We investigated the impact of Al toxicity on the P content of root apices of two tropical forage cultivars of the Brachiaria genus, grown in Al-containing low-ionic-strength nutrient solutions. Exposure to Al did not affect apical P concentrations in Al-resistant B. decumbens cv. Basilisk. In contrast to previous results obtained with other plant species, however, it caused a 70% decline in the apical P content of Al-sensitive B. ruziziensis cv. Common, despite the simultaneously increasing P levels in older root portions. This effect was largely due to a reduced accumulation of organically bound P, because less than 7% of the P in root apices was in the inorganic form in either species or treatment. The P content of root apices might be a useful indicator for evaluating the resistance of Brachiaria cultivars to prolonged Al stress.